Tìm x, biết
-3x²+5x=0
Tìm x biết:
\(a) x^2+3x-10=0 \)
\(b) x^2-5x-6=0\)
\(c) 2x^2+3x-2=0\)
a: Ta có: \(x^2+3x-10=0\)
\(\Leftrightarrow\left(x+5\right)\left(x-2\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=-5\\x=2\end{matrix}\right.\)
b: Ta có: \(x^2-5x-6=0\)
\(\Leftrightarrow\left(x-6\right)\left(x+1\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=6\\x=-1\end{matrix}\right.\)
Tìm x, biết
a, x (x - 3) - 2x + 6 = 0
b, (3x - 5) (5x - 7) + (5x +1) (2 - 3x)
Ta có : x(x - 3) - 2x + 6 = 0
<=> x(x - 3) - (2x - 6) = 0
=> x(x - 3) - 2(x - 3) = 0
=> (x - 2)(x - 3) = 0
\(\Leftrightarrow\orbr{\begin{cases}x-2=0\\x-3=0\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x=2\\x=3\end{cases}}\)
Tìm x biết
(X-2)^2+|x-y|=0
3x+2/5x+7=3x-1/5x+1
Tìm x biết:
a) 5x(x – 2) + 3x – 6 = 0
b) x 3 – 9 x = 0
Tìm x biết:
1) x (x-2016) + 2015 (2016-x) = 0
2) -5x (x-15) + (15-x) = 0
3) 3x (3x-7) - (7-3x) =0
1) x (x-2016) + 2015 (2016-x) = 0
x (x-2016) - 2015 (x- 2016) = 0
(x-2015)(x-2016) =0
\(\Rightarrow\orbr{\begin{cases}x-2015=0\\x-2016=0\end{cases}\Rightarrow\orbr{\begin{cases}x=2015\\x=2016\end{cases}}}\)
Vậy x= 2015; 2016
2) -5x (x-15) + (15-x) = 0
-5x (x-15) - (x-15) =0
(-5x -1) (x-15) =0
\(\Rightarrow\orbr{\begin{cases}-5x-1=0\\x-15=0\end{cases}\Rightarrow\orbr{\begin{cases}-5x=1\\x=15\end{cases}\Rightarrow}\orbr{\begin{cases}x=-\frac{1}{5}\\x=15\end{cases}}}\)
Vậy x= -1/5; 15
3) 3x (3x-7) - (7-3x) =0
3x(3x-7) + (3x -7) =0
(3x+1) (3x-7) =0
\(\Rightarrow\orbr{\begin{cases}3x+1=0\\3x-7=0\end{cases}\Rightarrow\orbr{\begin{cases}3x=-1\\3x=7\end{cases}\Rightarrow}\orbr{\begin{cases}x=-\frac{1}{3}\\x=\frac{7}{3}\end{cases}}}\)
Vậy x= -1/3 ; 7/3
tìm x biết:
a)x2 + 3x = 0 b) x3 – 4x = 0
c) 5x(x-1) = x-1 d) 2(x+5) - x2-5x = 0
e) 2x(x-5)-x(3+2x)=26 f) 5x.(x – 2012) – x + 2012 = 0
a) \(\Rightarrow x\left(x+3\right)=0\)
\(\Rightarrow\left[{}\begin{matrix}x=0\\x=-3\end{matrix}\right.\)
b) \(\Rightarrow x\left(x^2-4\right)=0\Rightarrow x\left(x-2\right)\left(x+2\right)=0\)
\(\Rightarrow\left[{}\begin{matrix}x=0\\x=2\\x=-2\end{matrix}\right.\)
c) \(\Rightarrow\left(x-1\right)\left(5x-1\right)=0\)
\(\Rightarrow\left[{}\begin{matrix}x=1\\x=\dfrac{1}{5}\end{matrix}\right.\)
d) \(\Rightarrow2\left(x+5\right)-x\left(x+5\right)=0\Rightarrow\left(x+5\right)\left(2-x\right)=0\)
\(\Rightarrow\left[{}\begin{matrix}x=-5\\x=2\end{matrix}\right.\)
e) \(\Rightarrow2x^2-10x-3x-2x^2=26\)
\(\Rightarrow-13x=26\Rightarrow x=-2\)
f) \(\Rightarrow\left(x-2012\right)\left(5x-1\right)=0\)
\(\Rightarrow\left[{}\begin{matrix}x=2012\\x=\dfrac{1}{5}\end{matrix}\right.\)
tìm x biết
a) \(x^2+5x=0\)
b)3x(x-1)=1-x
a)\(x^2+5x=0\Rightarrow x\left(x+5\right)\Rightarrow\left[{}\begin{matrix}x=0\\x+5=0\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}x=0\\x=-5\end{matrix}\right.\)
b)\(3x\left(x-1\right)=1-x\Leftrightarrow3x^2-3x-1+x=0\Leftrightarrow3x\left(x-1\right)+\left(x-1\right)=0\)
\(\Leftrightarrow\left(x-1\right)\left(3x+1\right)=0\Rightarrow\left[{}\begin{matrix}x-1=0\\3x+1=0\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=1\\x=-\dfrac{1}{3}\end{matrix}\right.\)
Tìm x biết 5x3 - 3x2 + 5x - 3 = 0
5x^3-3x^2+5x-3=0
5x^3+5x-3x^2-3=0
5x(x^2+1)-3(x^2+1)=0
(x^2+1)(5x-3)=0
x^2+1=0 hoặc 5x-3=0
x(vô nghiệm) hoặc x=3/5
a)Thực hiện phép tính:(3x+1)(3x-1)-(18x^3+5x^2-2x):2x
b)Tìm x biết:3x(x-2021)-x+2021=0
\(a,\left(3x+1\right)\left(3x-1\right)-\left(18x^3+5x^2-2x\right):2x\\ =\left(9x^2-1\right)-\left(9x^2+\dfrac{5}{2}x-1\right)\\ =9x^2-1-9x^2-\dfrac{5}{2}x+1=\dfrac{5}{2}x\)
\(b,3x\left(x-2021\right)-x+2021=0\\ \Rightarrow b,3x\left(x-2021\right)-\left(x-2021\right)=0\\ \Rightarrow\left(x-2021\right)\left(3x-1\right)=0\\ \Rightarrow\left[{}\begin{matrix}x=2021\\x=\dfrac{1}{3}\end{matrix}\right.\)
tìm x biết
a) x^2-3x=0
b) x+5x^2=0
a) \(x^2-3x=0\)
\(\Rightarrow x\left(x-3\right)=0\) \(\Rightarrow\orbr{\begin{cases}x=0\\x-3=0\end{cases}\Rightarrow}\orbr{\begin{cases}x=0\\x=3\end{cases}}\)
Vậy x = 0 hoặc x = 3
b) \(x+5.x^2=0\)
\(\Rightarrow x\left(1+5x\right)=0\Rightarrow\orbr{\begin{cases}x=0\\1+5x=0\end{cases}\Rightarrow\orbr{\begin{cases}x=0\\5x=-1\end{cases}\Rightarrow}\orbr{\begin{cases}x=0\\x=-\frac{1}{5}\end{cases}}}\)
Vậy x = 0 hoặc x =\(-\frac{1}{5}\)
a,\(x^2-3x=0\Leftrightarrow x\left(x-3\right)=0\Leftrightarrow\orbr{\begin{cases}x=0\\x-3=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=0\\x=3\end{cases}}}\)
vậy x=0;x=3
b,\(x+5x^2=0\Leftrightarrow x\left(1+5x\right)=0\Leftrightarrow\orbr{\begin{cases}x=0\\1+5x=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=0\\5x=-1\end{cases}\Leftrightarrow}\orbr{\begin{cases}x=0\\x=\frac{-1}{5}\end{cases}}}\)
vậy x=0;x\(=\frac{-1}{5}\)